Racing strategies and tactics for outdoor middle distance events - Makubuya, T.; Kaufman, M. (Techniques Magazine, 2018)
Athletes of all kinds are often challenged when deciding racing strategy and tactics for particular races. Obviously, no one suggestion will allow the athlete the ability to wane off the pressure often arising from the adrenaline that is secreted prior to the start or firing the gun. However, the decisions made from the start to the finish can have significant impacts on the outcome of the race. These decisions are often what dictates following conversations of regret or rejoice that these athletes have at the conclusion of their races with their coaches and teammates. Racing strategies and tactical decisions are tough to make for many athletes in the race, and require education and practice to become competent and confident. Through various ways, coaches can help their athletes in applying strategies that work best. Adhering to a certain routine and becoming confident with the results of a particular strategy is beneficial, but there may be times where athletes need to abandon what they are used to if they want to optimize their success. In this article, we offer suggestions on how coaches and athletes can utilize common racing strategies (which we will define as a general race plan) and race tactics (which we will define as specific actions) in middle distance events. The key to this however, is for the athlete to try out and figure out what works well for them based on how the race unfolds as well as the strengths and weaknesses possessed by themselves and their opponents.